Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Simplify -4x - x.
-5x
-4x
-3x **Weegy:** Simplifying
-4x + -1x + -5x + -4x + -3x
Combine like terms: -4x + -1x = -5x
-5x + -5x + -4x + -3x
Combine like terms: -5x + -5x = -10x
-10x + -4x + -3x
Combine like terms: -10x + -4x = -14x
-14x + -3x
Combine like terms: -14x + -3x = -17x
-17x **User:** Simplify 5x + 2x + 7x.
14x3
(14x)3
14x (More)

Question

Expert Answered

Updated 8/16/2014 4:10:57 PM

2 Answers/Comments

-4x - x = -5x

Added 8/16/2014 4:10:47 PM

This answer has been confirmed as correct, not copied, and helpful.

5x + 2x + 7x

= 7x + 7x

= 14x

= 7x + 7x

= 14x

Added 8/16/2014 4:10:57 PM

This answer has been confirmed as correct, not copied, and helpful.

56.32 kL = _____ L **Weegy:** 56.32 kiloliter = 56,320 liter (More)

Question

Expert Answered

Updated 4/24/2015 2:21:00 AM

0 Answers/Comments

6(A + 2) + 5A **Weegy:** Answer is 11A+12 Solution: 6(A + 2) + 5A 6A+12+5A 11A+12 **User:** 7(B + 3) + 2B **Weegy:** 7(B + 3) + 2B = 7B + 21 + 2B = 9B + 21 or 3(3B + 7) **User:** 8(C + 10) + 20 **User:** 5(x + 2) - 6 **Weegy:** | x - 1 | = 5 ===>
x - 1 = 5 or x - 1 = -5 through which we can get x = 6 or x = -4
**User:** 8(R + 6) - 2R **User:** 8(X + 6) - 2X **User:** 18 - 2[x + (x - 5)] **Weegy:** | x - 1 | = 5 ===>
x - 1 = 5 or x - 1 = -5 through which we can get x = 6 or x = -4
(More)

Question

Expert Answered

Updated 7/3/2014 9:06:10 AM

5 Answers/Comments

8(C + 10) + 20

= 8C + 80 + 20

= 8C + 100

= 8C + 80 + 20

= 8C + 100

Added 7/3/2014 9:03:22 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [7/3/2014 9:07:45 AM]

5(x + 2) - 6

= 5x + 10 - 6

= 5x + 4

= 5x + 10 - 6

= 5x + 4

Added 7/3/2014 9:03:49 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [7/3/2014 9:07:47 AM]

8(R + 6) - 2R

= 8R + 48 - 2R

= 6R + 48

= 8R + 48 - 2R

= 6R + 48

Added 7/3/2014 9:04:18 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [7/3/2014 9:07:50 AM]

8(X + 6) - 2X

= 8X + 48 - 2X

= 6X + 48

= 8X + 48 - 2X

= 6X + 48

Added 7/3/2014 9:05:17 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [7/3/2014 9:07:51 AM]

18 - 2[x + (x - 5)]

= 18 - 2(x + x - 5)

= 18 - 2(2x - 5)

= 18 - 4x + 10

= 28 - 4x

= 18 - 2(x + x - 5)

= 18 - 2(2x - 5)

= 18 - 4x + 10

= 28 - 4x

Added 7/3/2014 9:06:10 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/3/2014 9:08:32 AM], Unconfirmed by jeifunk [7/3/2014 9:11:07 AM], Confirmed by jeifunk [7/3/2014 9:11:23 AM]

0 questions answered

There are no comments.